Prevalence and Predictors of Post-traumatic Stress Symptoms among Uyghurs Abroad - Semire Erkuygur; Sena Akbay-Safi; Ibrahim Senay (Intervention Journal of Mental Health and Psychosocial Support in Conflict Affected Areas)
This study aimed to investigate the prevalence of post-traumatic stress symptoms (PTSS) and its correlations among Uyghurs abroad. The sample included 264 Uyghurs living in various countries. The data were collected between October and November 2022 through an online self-report survey including a demographic Information Form, Harvard Trauma Questionnaire (HTQ-5) and several questions about current events related to past traumatic experiences and social interaction. The prevalence of PTSS was 44%. A positive correlation was found between being intimidated or bothered by the Chinese authorities during the post-traumatic experience, and PTSS mean scores in the total sample (r = .137, p < .05). Being intimidated or bothered predicted PTSS among the participants who exhibited possible signs of post-traumatic stress disorder (PTSD; N = 116), and worrying about one’s own family was a predictor of PTSS symptoms in the total sample.